Implementasi Aplikasi Sakti Dan Span Dalam Penyusunan Laporan Keuangan - Ahmad Inzil Anwar; Miftahul Hadi (LPPM Universitas Nias Raya, 2022)
This study aims to determine how the application of SAKTI and SPAN applications in the preparation of financial statements at the KPPN Pontianak. This study uses a qualitative method. Data and information obtained in the form of primary data and secondary data. The data that has been obtained is then processed to produce a conclusion that the application of SAKTI and SPAN in the preparation of financial reports, the General Ledger and Reporting Module (GLP) business processes, and the division of user roles in the operation of SAKTI and SPAN are in accordance with applicable theories, regulations, and provisions. In the process of preparing financial reports, there are obstacles faced by users in operating SAKTI and SPAN, including the system experiencing lagging, the SAKTI application under maintenance.